Lexical Cohesion in the Lead and Headline of Newspaper Reports - Bílková, Tereza (Univerzita Pardubice, 2014)
This bachelor thesis is focused on the use of lexical cohesive ties in the lead and headline of newspaper reports. The theoretical part defines the concept of lexical cohesion and provides a list of lexical cohesive ties. Moreover, the language of newspaper reports is described and the role of the lead and headline is discussed. The practical part deals with the types and frequency of lexical cohesive ties in the lead and headline of newspaper reports.
Prostředky lexikální koheze v titulku a úvodu novinové zprávy
Keywords: lexical cohesion; lexical cohesive ties; newspaper reports; headline; lead; lexikální koheze; lexikální kohezní vazby; novinové zprávy; titulek; úvod